Perjalanan Pendampingan UMKM Opak Ashoy Sarongge Selama Dua Musim Community Development - Tritiara, Caroline; Dahlia, Dahlia; Oswald, Kenny; Rusli, Michael; Nobellenskvia, Vero; Chaiyadi, Ricky; Ortega, Owen; Lee, Michelle Angel; Carisya, Adilla Putri; Wijaya, Ivano; Giovanni, Jessica; Yudianto, Jovin; Yuliati, Retno (SULUH: Jurnal Abdimas, 2023)
Opak Ashoy Sarongge is a snack food product from Ciputri Village, Pacet District, Cianjur Regency, West Java. Opak Ashoy Sarongge was previously named Opak Ashoy and only had one product. The problem encountered by partners in the first year of assistance is that the entrepreneurial spirit has not yet developed, considering that partners are farmers. The problem in the second year is that there has not been a significant increase in product sales. Through the Community Development 2020 activities carried out by Prasetiya Mulya University, it is hoped that it can empower the community in developing the entrepreneurial spirit of partners and improve MSME businesses. The purpose of this activity is to explore partners' entrepreneurial potential and increase sales of partner products. The results of this activity show that in the first year of mentoring, partners show their potential for entrepreneurship. Meanwhile, the result of the second year of mentoring is that partners are more innovative in developing a variety of product flavors.